τ → π π π ντ decays and the a1(1260) off-shell width revisited - Gómez Dumm, Daniel Alberto (2010)
The τ → π π π ν τ decay is driven by the hadronization of the axial-vector current. Within the resonance chiral theory, and considering the large- N C expansion, this process has been studied in Ref. [1] (D. Gomez Dumm, A. Pich, J. Portoles, 2004). In the light of later developments we revise here this previous work by including a new off-shell width for the lightest a1 resonance that provides a good description of the τ → π π π ν τ spectrum and branching ratio. We also consider the role of the ρ ( 1450 ) resonance in these observables. Thus we bring in an overall description of the τ → π π π ν τ process in excellent agreement with our present experimental knowledge.